Manajemen Pelatihan Berbasis Kompetensi UPTD Balai Latihan Kerja Dinas Perindustrian dan Tenaga Kerja - Ismiati, Nanik; Egar, Ngasbun; Soedjono, Soedjono (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Abstract One of the efforts made by the state to improve existing human resources is to hold training accompanied by certification. Competency-based training is carried out for the purpose of improving the skills of workers so that they are truly competent in their fields in order to produce productive, skilled workers who can compete in the job market. The Pekalongan Industry Service formed the UPTD Work Training Center of the Pekalongan City Industry and Manpower Service as a Technical Implementation Unit in the field of training and skills to improve the capabilities of human resources in Pekalongan. The purpose of this study is to obtain an overview of competency-based training activities that have been held. The research method used is qualitative. The results of the study indicate that the planning of competency-based training at the UPTD Work Training Center of the Pekalongan City Industry and Manpower Service is good and can be used as a guide when implementing training. The competency-based training organization system at the UPTD Work Training Center of the Industry Service is good with human resources for training who have carried out their roles, duties and responsibilities according to their respective positions and duties. The implementation of training has been carried out in accordance with the regulations and guidelines that have been set so that training participants are guaranteed the competency standards they have according to the needs of the industry or company. The training monitoring system and reporting on the placement of training alumni are carried out once a month to ensure that alumni have used their training skills in their workplaces properly Keywords: Planning, Organizational, Training, Competence